Carvacrol: From Ancient Flavoring to Neuromodulatory Agent - Zotti, Margherita (Molecules, 2013)
Oregano and thyme essential oils are used for therapeutic, aromatic and gastronomic purposes due to their richness in active substances, like carvacrol; however, the effects of the latter on the central nervous system have been poorly investigated. The aim of our study was to define the effects of carvacrol on brain neurochemistry and behavioural outcome in rats. Biogenic amine content in the prefrontal cortex and hippocampus after chronic or acute oral carvacrol administration was measured. Animals were assessed by a forced swimming test. Carvacrol, administered for seven consecutive days (12.5 mg/kg p.o.), was able to increase dopamine and serotonin levels in the prefrontal cortex and hippocampus. When single doses were used (150 and 450 mg/kg p.o.), dopamine content was increased in the prefrontal cortex at both dose levels. On the contrary, a significant dopamine reduction in hippocampus of animals treated with 450 mg/kg of carvacrol was found. Acute carvacrol administration only significantly reduced serotonin content in either the prefrontal cortex or in the hippocampus at the highest dose. Moreover, acute carvacrol was ineffective in producing changes in the forced swimming test. Our data suggest that carvacrol is a brain-active molecule that clearly influences neuronal activity through modulation of neurotransmitters. If regularly ingested in low concentrations, it might determine feelings of well-being and could possibly have positive reinforcer effects.